A Study on Factors Influencing Mediators Behavior in Matrimonial Disputes Settlements Through Mediation in India - B, LEELESH SUNDARAM.; SUNDARAM, ASHA; GAYATHRI, R.; PRIYA, V. VISHNU (The journal of contemporary issues in business and government, 2020)
On the growing preferences of mediation over judicial resolution among parties for matrimonial disputes, various studies have hypothesized on effects and efficiency of mediation in matrimonial disputes and mediators. Though it is well founded that a mediator’s behavior is a subject of change, research has failed to recognize the dynamics in the behavior of mediators and the changes in the behavior of mediators. While a close understanding on the role of mediator and his behavior is attempted, an ambiguity arises with respect to reasons for changes in the mediator’s behavior, role of pre-existing, concurrent and background factors in the behavior of mediators. Therefore this research aims in identifying various factors influencing mediator’s behavior in matrimonial disputes. The study is carried out with the help of a convenient sampling method, having 419 sample sizes from a sample frame in the mediators office and chambers . The statistical tools used for the purpose of deriving results are complex graphs, independent t test, Pearson correlations, Mann Whitney Utest. Every mediator is likely to get influenced by Place and hygiene factors. The study was able to find out that there is a significant difference between the number of mediators in influencing the behavior of mediators. Thus the study makes a conclusion that there are various factors that tend to influence a mediator’s behavior in matrimonial dispute settlement processes which include psychological factors, social factors and environmental factors.